2005
DOI: 10.1289/ehp.7301
|View full text |Cite
|
Sign up to set email alerts
|

Nitromusk and Polycyclic Musk Compounds as Long-Term Inhibitors of Cellular Xenobiotic Defense Systems Mediated by Multidrug Transporters

Abstract: Synthetic musk compounds, widely used as fragrances in consumer products, have been detected in human tissue and, surprisingly, in aquatic organisms such as fish and mollusks. Although their persistence and potential to bioaccumulate are of concern, the toxicity and environmental risks of these chemicals are generally regarded as low. Here, however, we show that nitromusks and polycyclic musks inhibit the activity of multidrug efflux transporters responsible for multixenobiotic resistance (MXR) in gills of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
91
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 189 publications
(93 citation statements)
references
References 71 publications
2
91
0
Order By: Relevance
“…Recently, HHCB and AHTN were found to compromise the multixenobiotic defense system in marine mussels, suggesting they may play a role as chemosensitizers that enable toxic multixenobiotic resistance substrates to accumulate in cells (Luckenbach and Epel 2005;Luckenbach et al 2004). Given these recent mechanistic studies, endpoints that relate more directly to the mode of action of musks should be considered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, HHCB and AHTN were found to compromise the multixenobiotic defense system in marine mussels, suggesting they may play a role as chemosensitizers that enable toxic multixenobiotic resistance substrates to accumulate in cells (Luckenbach and Epel 2005;Luckenbach et al 2004). Given these recent mechanistic studies, endpoints that relate more directly to the mode of action of musks should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Luckenbach et al (2004) demonstrated that four polycyclic musks, including AHTN and HHCB, compromised multixenobiotic defense systems (mxr transporters) in the marine mussel Mytilus californianus in the μM range (200-2000 μg/L). A long-term loss of efflux transporter activity can result in continued accumulation of normally excluded toxicants even after direct exposure to the musk has ended, and thus, may increase an organisms susceptibility to other toxicants (Luckenbach and Epel 2005). …”
Section: Introductionmentioning
confidence: 99%
“…The inhibition of larval development in the calanoid copepod (Acartia tonsa) was associated with exposure to HHCB and AHTN (Wollenberger et al 2003). Multi-xenobiotic resistance in the gills of the marine mussel was inhibited by SM (Mytilus californianus) (Luckenbach and Epel 2005). Moreover, HHCB and AHTN have been shown to present both estrogenic and anti-estrogenic activity during in vitro and in vivo experiments using zebrafish (Danio rerio) (Schreurs et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…(5) There are further interactions of substances, e.g. musk compounds are known to inhibit cellular xenobiotic export systems [17]. (6) Cross-reaction is known e.g.…”
Section: Cosmetic Products Are Uniquementioning
confidence: 99%